Sociotechnical innovations that reduce greenhouse gas emissions for the Amazon - Clavijo, Neidy; Gómez, Thomas (2023)
In the face of the significant challenge posed by the ecological and social effects of climate change in the Amazon and its agri-food systems, there is high expectation regarding innovations that can be fostered and implemented for adaptation and mitigation. This urgency is also caused by the alarming changes in carbon reserves caused by deforestation in these forests. If this trend continues, the Amazon could become a significant contributor to greenhouse gas emissions. Additionally, rising temperatures, changes in precipitation patterns, and an increase in extreme weather events are expected to cause substantial damage and economic impacts, including biodiversity loss and species extinction in the region.